HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP INTERAKSI SOSIAL SISWA KELAS V UPT SPF SD NEGERI TIDUNG KOTA MAKASSAR - Amir Pada; Widya Karmila Sari Achmad; S.Palilati, Nurul Almasyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the intensity of social media use, the level of social interaction, and the relationship between the intensity of social media use and social interaction among fifth-grade students at UPT SPF SD Negeri Tidung, Makassar City. The approach used in this research is quantitative with a non-experimental correlational research design. Data were collected through questionnaires and observations distributed to a sample of 67 students selected using purposive sampling techniques. The data obtained were analyzed using descriptive and inferential statistics through the Pearson Product Moment correlation test. The results showed that the intensity of social media use among students was relatively high, with most students actively using social media in their daily lives, particularly applications such as WhatsApp, TikTok, Instagram, and YouTube. Meanwhile, the students' level of social interaction was categorized as moderate, indicating that their ability to interact directly was fairly good, although some students tended to be more active virtually than in face-to-face interactions. Inferential analysis revealed a strong positive relationship between the intensity of social media use and students’ social interaction. This means that the higher the intensity of students’ social media use, the higher their level of social interaction, both directly and indirectly through the social media platforms used by fifth-grade students at UPT SPF SD Negeri Tidung, Makassar City.